China's transboundary hydropower development at home and abroad: exploring the regulatory interface between international water law and international economic law - Wouters, Patricia; Daza-Clark, Ana Maria; Devlaeminck, David J. (Frontiers in Climate, 2024)
China, located upstream on most of the major transboundary waters shared with vast populations across Asia, is heavily invested in developing hydropower at home and abroad. Some of this hydropower development takes place on waters shared across national borders raising complex international issues, further exacerbated by economic, environmental, social, and increasingly urgent climate-change pressures. In such a context, where conflicts-of-use are almost certain to arise, it is essential to understand the rules that apply so as to enhance opportunities for enhanced transboundary water cooperation. This paper examines the rules of international water law and international economic law that apply to transboundary hydropower development, with a focus on China as one of the key actors in this field. The aim is to examine the regulatory interface of relevant legal frameworks with a focus on China’s approach to transboundary hydropower development at home and abroad. While international economic – and more specifically international investment law – is not directly concerned with international water law, host states and foreign investors must be informed, and take into account, the legal obligations governing transboundary waters. China’s position as a major water user (at home) and significant investor (abroad) on transboundary waters, makes it a unique case study for exploring the rules of international law that apply in two different regulatory settings. The work examines the rules of law in each of these domains and reveals the inapparent linkages across these seemingly unconnected areas of international regulation.